Control of formation process for the functional coating microstructures - Derevianko, O. I.; Kviatkovskyi, O. Ye. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The problem of motion control of many interacting particles in the Poincare section is discussed in the framework of molecular dynamics. The proposed approach provides an opportunity to consider one-parameter control for the transition from the chaotic to polyharmonic regime. Selecting a control parameter value allows to maintain the stability of the forming process for the coating's structural elements of PVD technology.